Validasi Dan Verifikasi Hasil Uji Sun Protection Factor (Spf) Pada Sediaan Sunblock Dan Sunscreen Bermerk Dengan Metode Spektrofotometri - rahayu artini yuan (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Tests for the determination of SPF value were calculated from the seven sunblock and brandes sunscreen preparation which were analyzed using 96% etanol solvent and kloroform, ranging from 17.21-26.88. The results of the VA-14 sample calculation have the lowest SPF value (SPF = 17.21) and the ES-30 sample has the largest SPF value calculation results from the seven samples (SPF ES-30 = 26.88). The seven samples are samples that have well-known brands in Indonesia. Of the seven cosmetics samples, six samples had a% recovery in accordance with the standard between 80-120%, but one product, namely SA-35, had a recovery rate of 73.23%. Organoleptic test results showed that the overall type of cream was m / a, fragrance, color from milky white, light brown, and light green. The pH value between 6.8-7.5 according to the quality standard of sunscreen preparations in SNI 16-4399-1966, the pH value for sunscreen preparations is 4.5-8.0. Thus, the results of the seventh pH of the sample are still within good standard limits for cream preparations containing sunscreen.